PENGEMBANGAN DESA AKAR-AKAR SEBAGAI DESA SENTRA HORTIKULTURAL BUAH-BUAHAN LAHAN KERING - Dewi, Mariska Sofiana; Riana, Nova; Yudiarsa, Galih; Anom, Putre; Rizfi, Chairil; Tejowulan, Sri (Universitas Mataram, 2024)
Akar Akar Village is mostly a dry land area with rainfall that only appears at the end of December and even in 2024 the first rain will appear at the beginning of January and will end sooner than other areas, thus this area is a dry area or has less access. water so that water problems are an important problem. This area is very suitable for the growth and production of fruit plants including grapes, longans, mangoes with premium quality results. Cultivating grapes has great advantages if people want to manage these plants and grapevines are very suitable on dry land such as in root villages and do not require a lot of water. The price of grapes is quite high and allows for a significant increase in income. The problems that have been identified are then carried out mapping of village potential which is carried out in socialization and village community empowerment activities which are carried out in 1 activity. In order to support community empowerment as an effort to improve the community's economy in the long term, the KKN group seeks to provide outreach regarding good and correct ways to cultivate grapes and hold field schools in vineyards to increase community knowledge. There are several grape plants that have been cultivated in every resident's yard. The grape seeds chosen for cultivation are imported types, because imported seeds are one of the seeds that will produce a higher market price compared to local seeds. This activity program is carried out to increase public knowledge about how to plant grapes correctly and be successful in harvesting grapes. Planting grapes can help a village become prosperous if the community already knows good and correct grape cultivation techniques and the potential of grapes as a profitable business